DESKRIPSI PENGUNJUNG RUMAH BACA TPA NURUL HIDAYATULLAH - Kurnia Ningsih; Eko Sri Wahyuni; Ruqiah Ganda Putri Panjaitan (Faculty of Teaching and Education, University of Wiraraja, 2017)
This study aims to determine the number of visitors to the small library of TPA Nurul Hidayatullah. The method in this study was a descriptive survey techniques. Based on visitor data is known that the number of visitors was increased and decrease at different condition. Number of visitor was increase when the new books or magazine come and it was decrease when the condition is not supporting. It can be concluded that to build interest in reading needs to be supported by the availability of reading material, as well as reading facilities and infrastructure.